2018
DOI: 10.1186/s40425-018-0374-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of WEE1 kinase and cell cycle checkpoint activation sensitizes head and neck cancers to natural killer cell therapies

Abstract: BackgroundNatural killer (NK) cells recognize and lyse target tumor cells in an MHC-unrestricted fashion and complement antigen- and MHC-restricted killing by T-lymphocytes. NK cells and T-lymphocytes mediate early killing of targets through a common granzyme B-dependent mechanism. Tumor cell resistance to granzyme B and how this alters NK cell killing is not clearly defined.MethodsTumor cell sensitivity to cultured murine KIL and human high affinity NK (haNK) cells in the presence or absence of AZD1775, a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…To overcome this requirement, haNKs, or high-affinity NK cells, are NK-92 cells engineered to express endoplasmic reticulum-retained IL-2(11). haNKs have demonstrated the ability to efficiently kill carcinoma cells at low effector-to-target ratios(12, 13). Irradiation of haNKs and haNK-derived cell products ensures short life span of these cells and allows for repeat administration with no risk of cellular engraftment and low risk of cytopenias in treated hosts(14, 27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this requirement, haNKs, or high-affinity NK cells, are NK-92 cells engineered to express endoplasmic reticulum-retained IL-2(11). haNKs have demonstrated the ability to efficiently kill carcinoma cells at low effector-to-target ratios(12, 13). Irradiation of haNKs and haNK-derived cell products ensures short life span of these cells and allows for repeat administration with no risk of cellular engraftment and low risk of cytopenias in treated hosts(14, 27).…”
Section: Discussionmentioning
confidence: 99%
“…NK-92 cells, derived from a Non-Hodgkin’s lymphoma patient, can be continuously expanded in culture and following irradiation, can be safely administered in high doses to patients with cancer(8-10). High-affinity NK (haNK) cells are NK-92 cells engineered to express endoplasmic reticulum-retained IL-2(11), have demonstrated potent effector function in numerous pre-clinical models(12, 13), and following irradiation, can also be safely administered in high doses to patients(14). haNKs represent an “off the shelf” NK cellular therapy available for pre-clinical and clinical study.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman et al recently utilized an inhibitor for the WEE1 kinase (AZD1775) on head and neck cancer cells, which reversed G2/M cell cycle checkpoint activation of the cancer cells, resulting in increased DNA damage and susceptibility to NK cell-mediated killing (318). Interestingly, DNA cell cycle checkpoint in this study did not impact surface expression of MHC-I, PD-L1, or NKG2D ligands (RAE, H60, MULT-1) on cancer cells, despite increasing their susceptibility to NK cells.…”
Section: Upregulation Of Nk Cell Ligandsmentioning
confidence: 99%
“…This study also reported evidence of immunologic memory after combination treatment 172 . AZD1775 also sensitises human head and neck cancer cells to avelumab, improving antibody‐dependent cellular cytotoxicity‐mediated killing of these cancer cells 173 . AZD1775 is being trialled as a monotherapy in various tumour types such as uterine cancer (NCT03668340) and relapsed small cell lung cancer (NCT02593019).…”
Section: Combination Of Immune Checkpoint Inhibitor Therapiesmentioning
confidence: 65%